2009
DOI: 10.1016/j.trstmh.2008.11.017
|View full text |Cite
|
Sign up to set email alerts
|

Platelet function and the von Willebrand factor antigen in the hepatosplenic form of schistosomiasis mansoni

Abstract: Forty-five individuals with hepatosplenic schistosomiasis mansoni were studied with the aim of measuring levels of von Willebrand factor antigen (vWF:Ag), detecting abnormalities in platelet morphology and aggregation, and identifying changes to surface antigens. Haemograms, platelet aggregation tests, flow cytometry investigations of CD41/CD42b antibody and vWF:Ag assays were performed. Mean platelet counts were low (77,522/mm3) and 82.2% of patients presented thrombocytopenia. An inverse relationship between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 16 publications
2
23
0
Order By: Relevance
“…In schistosomiasis, the changes of the intrahepatic biliary tree, either by ductal injuries caused by ovular reactions or arising from of PPF, could be the anatomical substrate for the increase of this enzyme (3,34) . The platelet count in the blood has been an indicator of severity in schistosomiasis by increasing the risk of bleeding, with its numerical reduction related to the presence of portal hypertension (8,31) and PPF (7) . Some schistosomiasis studies that evaluated platelets and other serum markers have reported lower platelet levels in patients with more advanced fibrosis (2,12,16) .…”
Section: Characteristics Of the Patientsmentioning
confidence: 99%
“…In schistosomiasis, the changes of the intrahepatic biliary tree, either by ductal injuries caused by ovular reactions or arising from of PPF, could be the anatomical substrate for the increase of this enzyme (3,34) . The platelet count in the blood has been an indicator of severity in schistosomiasis by increasing the risk of bleeding, with its numerical reduction related to the presence of portal hypertension (8,31) and PPF (7) . Some schistosomiasis studies that evaluated platelets and other serum markers have reported lower platelet levels in patients with more advanced fibrosis (2,12,16) .…”
Section: Characteristics Of the Patientsmentioning
confidence: 99%
“…Using ultrasound with the Niamey classification as the gold standard, correlations have been described between patterns of fibrosis and serum levels of IgG and hyaluronic acid (5,22) . Though, the determination of these substances requires sophisticated methods that are generally not available in simpler laboratories found in endemic regions for schistosomiasis.…”
Section: Discussionmentioning
confidence: 99%
“…Besides the proteins responsible for fibrogenesis others stemming from the degradation process of the extracellular matrix have been studied in the evaluation of fibrosis, such as hyaluronic acid, laminin and type IV collagen (10,16,19,27) . Likewise, the number of platelets is reported to be inversely correlated with the intensity of periportal fibrosis due to the sequestering of platelets in the splenic parenchyma stemming from splenomegaly (5,12,17,23) . Considering the scarcity of accurate data regarding the measurement of fibrosis using serum markers in patients with SM, the aim of this study was to correlate platelet count with both the periportal fibrosis pattern and spleen diameter as evaluated through an ultrasound exam.…”
Section: Correlation Between Platelet Count and Both Liver Fibrosis Amentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, an inverse relationship between spleen size and PLT was suggested by Correia et al (2009b).…”
Section: Serum Type VI Collagenmentioning
confidence: 99%